clinker & clustermap.js: automatic generation of gene cluster comparison figures - Gilchrist, Cameron L M; Chooi, Yit-Heng (Bioinformatics (Oxford, England), 2021)
Abstract Summary Genes involved in biological pathways are often collocalised in gene clusters, the comparison of which can give valuable insights into their function and evolutionary history. However, comparison and visualization of gene cluster similarity is a tedious process, particularly when many clusters are being compared. Here, we present clinker, a Python based tool and clustermap.js, a companion JavaScript visualization library, which used together can automatically generate accurate, interactive, publication-quality gene cluster comparison figures directly from sequence files. Availability and implementation Source code and documentation for clinker and clustermap.js is available on GitHub (github.com/gamcil/clinker and github.com/gamcil/clustermap.js, respectively) under the MIT license. clinker can be installed directly from the Python Package Index via pip. Supplementary information Supplementary data are available at Bioinformatics online.